On fixed point theorems for generalized weakly CE-contraction mappings on metric spaces. Issue 3 (2nd April 2020) - Stella Eke, Kanayo; Bishop, Sheila A.
Abstract: A new class of generalized weakly CE -contraction mappings is introduced in this research work. Some fixed point theorems for this generalized weakly CE –contraction mappings are proved in the context of metric spaces. An illustration to validate our results is provided. The results obtained in this work are generalizations and extensions of some related works in the literature.